Choice of School in Poor Neighborhoods: Results from a Qualitative Study [la Elección de Escuela en Sectores Pobres: Resultados de Un Estudio Cualitativo] - Cordoba-Calquin, C (Pontificia Universidad Catolica de Valparaiso, 2014)
One of the assumptions on which our system of subsidy per student is based is that families choose school according to their quality. To study how this assumption works in poor neighborhoods, we conducted twenty-six group interviews with mothers that send their children to municipal and private subsidized schools within a working-class urban commune of the Metropolitan Region in Chile. We focus the presentation of results on the criteria and sources of information people use when choosing a school. We conclude that: i) family preferences are limited by financial resources; ii) nearness and quality of education drive choice in a complex process where the SIMCE test has no relevant role; and iii) the type of student attending a particular school is strongly associated with the quality that the family attaches to that school. We argue that families from poor neighborhoods do play an active role in school choice.